Site-directed mutagenesis of E2 protein nanocage for the tunable display of siRNA - Zennathul Firdous Mohamed Barak (2016)
Melasma is characterized by brown and tan discoloration of the skin, often present in women. It is a chronic disease that affects the quality of life. Although there are existing treatments such as chemical peels and creams for this skin disease, they are not effective nor satisfactory. Hence, there is a need to find a new treatment that can improve this condition. siRNAs have been increasingly popular as a potential therapeutic modality for skin diseases. However, one of the biggest problem of siRNA is its inability to penetrate the stratum corneum of the skin layer effectively. E2 protein nanocages are explored, in this report, as a carrier for the siRNA strand to deliver the siRNA into viable cells. To increase the number of siRNAs each nanocage can carry and to increase the efficacy of the treatment, certain positions of amino acid residues on the outer surface can be changed to cysteine residues. The objective of this project was to mutate the E2 protein nanocage at certain positions to introduce cysteine, and subsequently to produce and characterize the mutated nanocages. This was done by purifying the protein using FPLC and characterizing via DLS and TEM. Results show that the mutated E2 nanocages behave in a similar manner to wildtype E2 nanocages. The optimum conditions for heat treatment after sonication was found to be at 75˚C at 25 minutes and the hydrodynamic size was found to be about 26.11nm in diameter.